Dietary consumption of meat, fat, animal products and advanced glycation end‐products and the risk of Barrett's oesophagus. Issue 7 (19th August 2013) - Jiao, L.; Kramer, J. R.; Chen, L.; Rugge, M.; Parente, P.; Verstovsek, G.; Alsarraj, A.; El‐Serag, H. B.
Summary: Background: Advanced glycation end‐products (AGEs) are found in high quantity in high‐fat foods and meat cooked at high temperature. AGEs have been shown to contribute to chronic inflammation and oxidative stress in humans. Aim: To investigate the associations between consumption of meat, fat and AGEs, and the risk of Barrett's oesophagus (BO). Methods: We conducted a case–control study using data from the patients who were scheduled for elective esophagogastroduodenoscopy (EGD) and from a random sample of patients who were identified at primary care clinics. Daily consumption of meat, fat and Nε‐(carboxymethyl) lysine (CML), a major type of AGEs, was derived from the food frequency questionnaire (FFQ). Multivariate logistic regression models were used to estimate the odds ratio (OR) and its 95% confidence interval (CI) for BO. Results: A total of 151 cases with BO and 777 controls without BO completed the FFQ. The multivariate OR (95% CI) for BO was 1.91 (1.07–3.38) for total meat, 1.80 (1.02–3.16) for saturated fat and 1.63 (0.96–2.76) for CML‐AGE, when the highest tertile of intake was compared with the lowest. The association for total meat was attenuated to 1.61 (0.82–3.16), and that for saturated fat to 1.54 (0.81–2.94) after adjusting for CML‐AGE. Conclusions: Higher consumption of total meat, saturated fat or possibly CML‐AGE was associated with an increased risk of Barrett's oesophagus. CML‐AGE may partly explain the association between total meat and saturated fat consumption and the risk of Barrett's oesophagus.